From monocular photograph to angle lambda: A new clinical approach for quantitative assessment. Issue 3 (3rd July 2022) - Rateaux, Maxence; Bremond-Gignac, Dominique; Robert, Matthieu P.
ABSTRACT: Angle lambda assessment is essential in pediatric and strabismus practice. An abnormal angle lambda will modify the visual appearance of a strabismus or mimic one. Currently, angle lambda can be assessed by corneal topographs. Unfortunately, the use of these devices remains limited in the context of a strabismus clinic. Herein, we propose an easy, low cost, and reproducible method for angle lambda quantification, based on monocular photographs. Monocular pictures were taken by using a camera with a ring flash, centered by a fixation point. A digital evaluation analyzed the position of the corneal reflex on the pupil diameter. Using a trigonometric formula, the resulting ratio was converted into the value of angle lambda. This method was tested on 20 healthy eyes, on two successive couples of pictures, to evaluate its repeatability. Assessment using Pentacam was performed for comparison. The mean value of angle lambda was +2.61° ± 2.92° and 2.63° ± 2.85° in both picture series, respectively, and Lin's repeatability coefficient was 0.99 – with a systematic deviation of −0.071° compared to Pentacam assessment. Angle lambda distribution was in range with values from the literature. This new method allows for angle lambda assessment without requiring a specific device and can be used in strabismus and pediatric clinics.